Research on the Antimicrobial Activity of Frankincense from Boswellia serrata Roxb - Mohammad Salim; Tanya Kharadi; Farhat Jahan (Recent Trends in the Study of Botanical Research Volume - 1, 2023)
The current study focuses on conducting In-vitro experiments to assess the antimicrobial properties of frankincense from Boswellia serrata. Various concentrations (25, 50, 75, and 100 mg/ml) were tested to evaluate the effectiveness against Gram-positive bacteria like Bacillus subtilis, Staphylococcus aureus, and Streptococcus pneumoniae, as well as Gram-negative bacteria including Escherichia coli and Klebsiella pneumoniae. For microbes like Enterobacter aerogenes, Pseudomonas aeruginosa, and Proteus vulgaris, inhibition zones were measured and compared to the positive control antibiotic Ciprofloxacin (5ug/ml), and negative control DMSO. The results demonstrated significant antimicrobial activity. The frankincense extracts exhibited antimicrobial effects similar to the standard, suggesting their potential use in treating diseases caused by these bacterial strains.